2020
DOI: 10.1177/1465750320921296
|View full text |Cite
|
Sign up to set email alerts
|

Craft beer sector collaboration in North East Scotland: The role of individual success

Abstract: Our understanding of craft brewing is beginning to grow and a key theme to emerge from this artistic and intrinsically creative sector is the dependence on collaboration between entrepreneurial agents. In the North East of Scotland, the growth in craft beer is also recognised to come from a deep rooted collaboration, as a reaction to and in resistance of large mainstream competition. However, one such enterprise, BrewDog, has grown to achieve global reach to rival that of the large-scale brewers the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…In support of Cunningham and Barclay (2020), our brewers point to a collective desire to bring more knowledgeable custom into the craft beer market (Figure 3). Much of this desire to 'educate' a latent customer base is rooted in a dissatisfaction with mainstream brewers.…”
Section: -Differentiation Within the Marketmentioning
confidence: 87%
See 2 more Smart Citations
“…In support of Cunningham and Barclay (2020), our brewers point to a collective desire to bring more knowledgeable custom into the craft beer market (Figure 3). Much of this desire to 'educate' a latent customer base is rooted in a dissatisfaction with mainstream brewers.…”
Section: -Differentiation Within the Marketmentioning
confidence: 87%
“…Second, we integrate these findings with the extant literature to build a conceptual model on the nature of collaboration in the craft beer sector. As such, we develop from the initial exploratory work of Cunningham and Barclay (2020) to build an explanatory model to frame future research.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in craft beer tourism research, the social and economic dimensions are equally substantial domains and have been addressed in several studies in different contexts [28,29]. For instance, extant studies showed how craft beer tourism can foster social sustainability through localized collaboration between craft breweries and local communities to create various craft beer tourism forms such as brewery visitations, beer trials, and beer festivals [30,31]. In addition, economic sustainability in craft beer tourism can emerge from fostering innovative business strategies [17].…”
Section: Craft Beer Tourism As An Opportunity For Sustainable Businessmentioning
confidence: 99%
“…Because craft beer brewing is considered an artwork or a form of artisan entrepreneurship [31], many craft beer consumers become drawn to their favorite artists and have devoted themselves to brands. Attending a festival that has multiple brewers opens opportunities for the attendees to interact with and support their favorite craft brewers and brands.…”
Section: A Proposed Fifth Domain Of Tourism Experiencementioning
confidence: 99%